THE IMPLEMENTATION OF THE WIN-LOSE APPROACH INORGANIZATIONS: IMPACT ON CONFLICT RESOLUTION ANDEMPLOYEE SATISFACTION - Marmullaku, Arsim (E-Journal VFU, 2024)
This study aims to analyze the complex aspects of conflict, taking into accountboth its effects. It also examines potential conflict-resolution strategies, the methodologies used inthem, and the key elements that have a significant impact on the resolution of conflicts. Kosovo isthe main focus of the study and serves as an important case study for these questions. In terms ofmethodology, a quantitative approach was used, involving the collection of data using carefullycreated questionnaires. The sample included leaders from the employee cohort designed to reflectthe organizational landscape. There were 340 organizational leaders who participated in thesurvey. The research includes a presentation of descriptive data analysis and findings. However,the study does not provide evidence to support the idea that one of the conflict-resolution strategies(Layout, Rotacion, or Transfer) could achieve the desired outcome.
Keywords: Conflict; Management; Efects